Fatty liver disease as a predictor of local recurrence following resection of colorectal liver metastases. Issue 6 (28th January 2013) - Hamady, Z. Z. R.; Rees, M.; Welsh, F. K.; Toogood, G. J.; Prasad, K. R.; John, T. K.; Lodge, J. P. A.
Abstract Background Obesity and tissue adiposity constitute a risk factor for several cancers. Whether tissue adiposity increases the risk of cancer recurrence after curative resection is not clear. The present study analysed the influence of hepatic steatosis on recurrence following resection of colorectal liver metastases. Methods A prospective cohort of patients who had primary resection of colorectal liver metastases in two major hepatobiliary units between 1987 and 2010 was studied. Hepatic steatosis was assessed in non‐cancerous resected liver tissue. Patients were divided into two groups based on the presence of hepatic steatosis. The association between hepatic steatosis and local recurrence was analysed, adjusting for relevant patient, pathological and surgical factors using Cox regression and propensity score case‐match analysis. Results A total of 2715 patients were included. The cumulative local (liver) disease‐free survival rate was significantly better in the group without steatosis (hazard ratio (HR) 1·32, 95 per cent confidence interval 1·16 to 1·51; P < 0·001). On multivariable analysis, hepatic steatosis was an independent risk factor for local liver recurrence (HR 1·28, 1·11 to 1·47; P = 0·005). After one‐to‐one matching of cases (steatotic, 902) with controls (non‐steatotic, 902), local (liver) disease‐free survival remained significantly better in the group without steatosis (HR 1·27, 1·09 to 1·48; P = 0·002). Patients with steatosis had a greater risk of developing postoperative liver failure (P = 0·001). Conclusion Hepatic steatosis was an independent predictor of local hepatic recurrence following resection with curative intent of colorectal liver metastases.